The Impact of Participation of Palestinian Players inside Palestinian Professional Football League on the Cohesion of the Team from the Point of View of Technical Staff - Eyad Yousef; Mahmoud Kayed; Zyad Irmaily (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims to identify the effect of the participation of Palestinian players in the Palestinian professional football league on the cohesion of the team from the point of view of the technical staff. In the study, a descriptive survey method was used for its relevance to its nature on a sample of (49) technicians working in the technical bodies in the Palestinian Professional Football League (technical director, assistant coach, and guard coach), during the 2018/2019 sports season. A questionnaire was also used that included (25) paragraphs. The results of the study indicated that the spirit of unity and intimacy was very great among team members, and that professional players were interested in the results of other teams in the Palestinian League, and that they tended to evade responsibility when the team's results were bad. The results also showed that there is a sense of jealousy from the non-professional players towards the professional players. The study recommends the need to enhance the spirit of unity and intimacy among the players of one team, and to work on clarifying the roles between each of the players and the coach in order to avoid jealousy among the players.